SMEs in Malaysia: History and Development / Dr Salwa Muda and Musliha Musman - Muda, Salwa; Musman, Musliha (UiTM Cawangan Negeri Sembilan Kampus Seremban, 2022)
Small and Medium sized enterprises (SMEs) have significantly contributed to the Malaysian economy since the early dependence phase, which relied on the agriculture sector as the main source of the nation’s income until today’s economy that depends on manufacturing and services sectors. SMEs play vital roles as the engine of growth through employment opportunities, major sources of technological and product innovation, and poverty reduction through providing employment to poor and low-income workers especially in poor regions and rural areas. Besides the functions of SMEs as an important tool for a competitive and efficient market, they also prove their significant contribution in stimulating Malaysia’s economic expansion and fulfilling the socio-objectives. Despite their small size, the contribution of the Malaysian SMEs in enhancing the economic development and fulfilling the social needs of the nation indicates their important role in strengthening the country to face the resilient challenges in today’s knowledge economy. SMEs in Malaysia are defined according to the annual turnover or number of full-time employees. Starting from 2005, a formal definition of SMEs endorsed by NSDC is based on the annual turnover and number of full-time employees that have been used by ministries, agencies, financial institutions and regulators involved with SME development programmes.